Caregiver perceptions of end-of-life care in patients with high-grade glioma. Issue 2 (20th November 2020) - Fortunato, John T; Van Harn, Meredith; Haider, Sameah A; Phillips, Joel; Walbert, Tobias
Abstract: Background: Patients dying from high-grade gliomas (HGG) suffer from high symptom burden in the end-of-life (EoL) phase. Family caregivers are most informed about the patient's symptoms and disease course. The aim of this study is to assess caregiver perception on quality of EoL care of HGG patients. Methods: Caregivers prospectively participated in the Toolkit After-Death Bereaved Family Member Interview, part of the Toolkit of Instruments to Measure End-of-Life Care (TIME survey). This validated survey assesses EoL care in areas such as physical comfort and emotional support, advance care planning, focus on the individual, attention to family, and coordination of care. The quality of EoL care was measured by domain scores (0 = care was always optimal, 1 = care was always suboptimal) or with a 0-10 scale. Results: Of the 55 enrolled family caregivers, 44 completed the interview and rated the overall care high (8.90 ± 1.36/10), perceived that patients' wishes were respected (9.46 ± 0.95) and that they died in dignity (9.65 ± 0.98). Caregivers perceived high satisfaction with information and decision-making (0.18), advance care planning (0.19), focus on the individual (0.16), and care coordination (0.11). Attention to family (0.25) needed improvement. Only 41% of caregivers were confident that they knew what to do at the time of death and 46% felt that the healthcare team did not provide them with someone to turn to in distress. Conclusions: Caregivers reported high overall satisfaction with EoL HGG care, though attention to family and communication needed improvement. Focus should therefore be on improved caregiver communication to improve EoL care, caregiver burnout, and bereavement in HGG populations.